ANALYSIS STUDENT’S SPEAKING PERFORMANCE AS AN ACADEMIC SPEAKER’S PRACTICE - Selina Dwi Anggini; Arjulayana - Arjulayana (Universitas Muhammadiyah Tangerang, 2021)
Speaking is a productive skill with requires the interactive and performance process. To be able to improve and represent student’s capability in their speaking skill, student also need to drill and practice their speaking as the academic presenter, because if they able to speak academically, their speaking skill will get well improvement automatically. This research is aimed to investigate student’s speaking performance while they have academic speaking practice. The population of this research is 4th semester student of Universitas Muhammadiyah Tangerang, located in Cikokol-Tangerang. The sample is single sample. To find the data, researcher use video record originally from the speaker then doing the analysis with triangulation validity. This research showed that students speaking performance is need to be treating well, especially in their self-confident and vocabulary master, because it will be impossible for them to be a good speaker if they have lots of anxiety.